Construction Experience on Cloud Computing Platform of Enterprise Information System - Qian Wang; Lian Zou (Dianxin kexue)
During the infrastructure construction of enterprise information system，cloud computing technology was used to abstract the logic of traditional physical computing resources，unify and integrate，reconstruct flexibly it，in order to improve resource utilization，reliability and manageability.By using more mature VMware virtualization solution，the goal initially was achieved.Meanwhile，a complete procedure was found which could not only lead to safe and efficient transition to the cloud platform，but also maximize the utilization of existing resources.Thus，the construction of cloud computing platform of is necessary and feasible.Compared with traditional infrastructure，cloud computing platform has obvious advantages in resources utilization，energy saving，cost reduction，management facilitation，it can bring good profound benefits for enterprise.